Differences in Trabecular Microstructure Between Black and White Women Assessed by Individual Trabecular Segmentation Analysis of HR‐pQCT Images. (18th January 2017) - Putman, Melissa S; Yu, Elaine W; Lin, David; Darakananda, Karin; Finkelstein, Joel S; Bouxsein, Mary L
ABSTRACT: Black women have lower fracture risk compared with white women, which may be partly explained by improved volumetric bone mineral density (vBMD) and bone microarchitecture primarily within the cortical bone compartment. To determine if there are differences in trabecular microstructure, connectivity, and alignment according to race/ethnicity, we performed individual trabecular segmentation (ITS) analyses on high‐resolution peripheral quantitative computed tomography (HR‐pQCT) scans of the distal radius and tibia in 273 peri‐ and postmenopausal black ( n  = 100) and white ( n  = 173) women participating in the Study of Women's Health Across the Nation in Boston. Unadjusted analyses showed that black women had greater trabecular plate volume fraction, plate thickness, plate number density, and plate surface area along with greater axial alignment of trabeculae, whereas white women had greater trabecular rod tissue fraction ( p  < 0.05 for all). Adjustment for clinical covariates augmented these race/ethnicity‐related differences in plates and rods, such that white women had greater trabecular rod number density and rod‐rod connectivity, whereas black women continued to have superior plate structural characteristics and axial alignment ( p  < 0.05 for all). These differences remained significant after adjustment for hip BMD and trabecular vBMD. In conclusion, black women had more plate‐like trabecular morphology and higher axial alignment of trabeculae, whereas white women had more rod‐like trabeculae. These differences may contribute to the improved bone strength and lower fracture risk observed in black women. © 2016 American Society for Bone and Mineral Research.